Abuse of power selected works on the law and constitution - Thomas, Tommy (Strategic Information and Research Development Centre, 2016)
"Amongst the select group of constitutional law advocates in Malaysia, Tommy Thomas ranks among the best - fearless, dedicated, committed and vocal in his decades-old pursuit to entrench respect for fundamental rights and liberties for the ordinary Malaysiań⁰ŒThis timely collection of essays should be read by lawyers and non-lawyers alike for its valuable insights into important constitutional issues, and for the thinking jurist, it will serve as a beacon of conscience into what is right, correct and proper under the Constitution"--Dato' Mohamad Ariff Yusof, Retired Judge of the Court of Appeal--Back cover